Analysis of Leading Economic Sectors in Jayapura City - Charley M. Bisai; Risa Alifia Maharani; Sarlota A. Ratang; Balthazar Kreuta; Antonia Klara; Marsi Adi Purwadi (GoAcademica Research & Publishing, 2025)
This study aims to analyze the sectoral classification in Jayapura City and determine the economic sectors that can become the mainstay sectors in the Jayapura City economy during the period 2011-2023. The analysis is conducted based on Gross Regional Domestic Product (GRDP) data based on sector contributions to growth, the Growth Ratio Model, and overlay analysis. Data are obtained from official sources, such as publications of the Central Statistics Agency and regional economic reports. Based on the Growth Ratio Model (MRP), sectors in Jayapura City can be classified into several categories. Sectors that fall into classification I, or